Direct Measurements of Synchrotron-emitting Electrons at Near-Sun Shocks - Jebaraj, I. C.; Agapitov, O. V.; Gedalin, M.; Vuorinen, L.; Miceli, M.; Cohen, C. M. S.; Voshchepynets, A.; Kouloumvakos, A.; Dresing, N.; Marmyleva, A.; Krasnoselskikh, V.; Balikhin, M.; et al. (American Astronomical Society, 2025)
In this study, we present the first-ever direct measurements of synchrotron-emitting heliospheric traveling shocks, intercepted by the Parker Solar Probe (PSP) during its close encounters. Given that much of our understanding of powerful astrophysical shocks is derived from synchrotron radiation, these observations by PSP provide an unprecedented opportunity to explore how shocks accelerate relativistic electrons and the conditions under which they emit radiation. The probe's unparalleled capabilities to measure both electromagnetic fields and energetic particles with high precision in the near-Sun environment has allowed us to directly correlate the distribution of relativistic electrons with the resulting photon emissions. Our findings reveal that strong quasi-parallel shocks emit radiation at significantly higher intensities than quasi-perpendicular shocks due to the efficient acceleration of ultrarelativistic electrons. These experimental results are consistent with theory and recent observations of supernova remnant shocks and advance our understanding of shock physics across diverse space environments.